Eosinophilic esophagitis in children with esophageal atresia. Issue 4 (1st June 2014) - Dhaliwal, J.; Tobias, V.; Sugo, E.; Varjavandi, V.; Lemberg, D.; Day, A.; Bohane, T.; Ledder, O.; Jiwane, A.; Adams, S.; Henry, G.; Dilley, A.; et al.
Summaryy: Eosinophilic esophagitis (EoE ) has only rarely been reported in esophageal atresia (EA ) patients. A retrospective case analysis of all EA patients born at our center between J anuary 1999 and A pril 2012 was performed. A total of 113 of patients were identified; 10 patients were excluded as a result of inadequate data. Eighteen patients (17%) were diagnosed with EoE . The average number of eosinophilis was 30/high-power field (HPF ) (19/HPF –80/HPF ). The median age for diagnosis of EoE was 1 year and 6 months (8 months–8 years and 7 months). Children with EoE had a significantly greater incidence of reflux symptoms, dysphagia, tracheomalacia, and 'hypoxic spells' ( P < 0.05). EoE patients also underwent significantly more surgery including fundoplication and aortopexy when compared with those without EoE ( P < 0.0001). Although the incidence of gastrostomy was greater in the EoE group (33% vs. 13%), this was not statistically significant. Half of the EoE patients had a coexisting atopic condition at time of diagnosis. The commonest condition was asthma 7/18 (38%) followed by specific food allergy 6/18 (33%). EoE was treated in 11 patients with either swallowed fluticasone or budesonide slurry. All improved clinically. Histologically, five had complete resolution and six had partial improvement. Six children with EoE were treated with acid suppression alone. All improved clinically, and 5/6 had subsequent histological resolution. One child who received acid suppression and an exclusion diet also improved. Seven patients (38%) had an esophageal stricture at time of EoE diagnosis. Five were dilated at time of the initial endoscopy, prior to the diagnosis of EoE being available. Two patients had resolution of their strictures on medical treatment of their EoE alone and did not require further dilatation. EoE was seen in 17% of children with EA in this study. EoE should be considered in EA patients with persistent symptoms on standard reflux treatment, increasing dysphagia, and recurrent strictures.